PERILAKU FRAUD MAHASISWA DAN PERSEPSINYA TERHADAP ASPEK-ASPEK UMUM ETIKA BISNIS DAN TUJUAN PENDIDIKAN ETIKA PROFESI AKUNTANSI DITINJAU DARI JENIS KELAMIN - Annisa Asriati; Hajan Hidayat (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2018)
Students reached education ethics business with hope students will become an accountant without breaking ethics and work professionally. This study aims to see how perception students on the basis of gender to general aspects of business ethics, importance of the objectives of accounting ethics education and how do behavior students based on the types of fraud. The sample in this research is 499 students of the night class of accounting study program at an accredited university in Batam City. Testing the hypothesis in this study using a mann withney u test and descriptive statistics in SPSS 17.00. The results show that there are differences in perception between male students and female students of general aspects of business ethics and importance of the objectives of accounting ethics education. Most students considered it is important but most students has admitted that they have commits fraud based on the type of fraud internal. A student who work in the bank, student semester 1 and semester 3, Students who have received lecture business ethics and student man Dominated in the category of fraud. Limitations of this study is sample use only students of the night class of accounting study program in Batam alone. The provision of the science more in-depth about ethics business and also study of ethics are need to. Suggestions for further research is sample examined across extend, can add external factors that determines fraud behavior and for research on fraud that has happened.